Implantable bone conduction devices enhance functional ear reconstruction in patients with pediatric microtia - Chen, Ying; Li, Chen-long; Ren, Liu-Jie; Wu, Xu; Gao, Na; He, Ai-juan; Fu, Yao-yao; Zhu, Ya-ying; Zhang, Tian-yu (Frontiers in Pediatrics, 2025)
PurposeThis study evaluated the audiometric outcomes and complications of simultaneous bone conduction device (BCD) implantation and auricular reconstruction, and the comparative effectiveness of three BCDs.MethodsIn total, 41 patients with bilateral microtia (ranging from 8 to 16 years old) who underwent combined surgery from January 2018 to January 2024 were retrospectively analyzed. Audiometric parameters (free-field thresholds and speech recognition scores) and complications were compared across the groups of patients who received the Baha Attract (n = 13), Sophono (n = 18), and Bonebridge (n = 10) devices.ResultsSignificant improvements occurred in aided vs. unaided conditions, with mean free-field threshold values of 57.6 ± 7.42 vs. 22.19 ± 6.40 dB (p < 0.001) and speech recognition threshold values of 69.42 ± 4.21 vs. 39.16 ± 6.78 dB (p < 0.001). No significant inter-group differences emerged in hearing gain (p > 0.05). Device-related complications included transient skin reactions, hematoma, and pressure erythema, and all were resolved conservatively. The patients’ hearing threshold in a free field and speech recognition in quiet tests significantly improved after being implanted with the Baha Attract, Sophono, or Bonebridge hearing aid. There was no significant difference in hearing gain across frequencies between the subgroups. No patient in any of the subgroups reported major adverse events that affected the safety of the reconstructed auricle or the implant after the combined surgery.ConclusionThe three implants demonstrated satisfactory hearing performance in children with bilateral microtia. Combined BCD implantation and auricle reconstruction surgery was shown to be safe and effective.